PENYULUHAN HUKUM TERHADAP PENGATURAN NIKAH SIRI DI DALAM SISTEM HUKUM DI INDONESIA - Munajah Munajah; Yati Nurhayati; Muthia Septarina; Nahdhah (Jurnal Pengabdian Sumber Daya Manusia, 2021)
Community service at Pondok Tahfidz Madinatul Qur'an Banjarmasin which is aimed at the students of Pondok Tahfidz, aims to provide knowledge of the legal consequences arising from unregistered marriages. Lack of knowledge about the consequences of unregistered marriages is the main factor in the many practices of unregistered marriages that occur in society. This community service entitled "The Law of Siri Marriage in the Legal System in Indonesia (Legal Counseling at Pondok Tahfidz Madinatul Qur'an Banjarmasin)" is expected to provide an understanding of the students, especially in the area of ??Pondok Tahfidz Madintul Qur'an Banjarmasin on the consequences of unregistered marriage. So that with this service, it can reduce the practice of unregistered marriage in the Banjarmasin community in particular. The method used in this community service uses a sociological approach where the implementation is through counseling and lecture methods at the target location. The result of this trial is that there are conditions where people do not understand the legal consequences of unregistered marriages, especially for wives and children born from unregistered marriages.